Efeito do processo de auto-hidrólise e caracterização química da madeira de Eucalyptus grandis x Eucalyptus urophylla e Eucalyptus grandis - Morais, Alaine Patrícia da Silva [UNESP] (2015)
The paper industry has been focusing on current studies that seek alternatives for separating wood into its components, cellulose, hemicellulose, lignin and extractives; they hiding the various biorefinery opportunities by integrating production processes of fuels and chemicals from biomass. The solubilization of hemicelluloses by auto-hydrolysis has been proposed as the first step in biorefinery. And the extracted materials with autohydrolysis (auttohydrolysed liquors) can be used to produce biofuels and chemicals. Thus, this study evaluated the effect of temperature and time in autohydrolysis of Eucalyptus urograndis and Eucalyptus grandis possible to obtain kinetic data on the behavior of chemicals (extractives, lignin, holocellulose, hemicelluloses and cellulose) and also income and crystallinity index, to establish the points of maximum extraction of hemicelluloses prehydrolysed material. The experiments were performed in E. urograndis and E. grandis samples taken as a control (non-hydrolyzed) and prehydrolyzed. The material was autohydrolyzed minirreatores at different temperatures (110, 130, 150, 170 and 190 °C) to achieve different times (0, 5, 15, 30, 60, 120 and 150 minutes). In each minireactor was used to liquor ratio: wood (10: 1 L: kg dry wood). The results showed that the variables (temperature and time), influence on the yield; with decreasing lignin content of the sawdust was autohydrolyzed an increase in the extractives content; only a small amount of cellulose is removed compared hemicelluloses and a quick difference occurred in the cellulose crystallinity index between treatments. It is concluded that with E. urograndis and E. grandis sawdust autohydrolysis can drastically affect treatment without lignin and cellulose.